A Dragon Kiln in the Americas: European-American Innovation and African-American Industry. (4th May 2017) - Calfas, George
ABSTRACT: Archaeological investigations at the Pottersville kiln site in Edgefield, South Carolina in 2011 sought to identify the dimensions of the kiln and any architectural features associated with that structure's design. Locating and identifying key architectural elements would allow for a better understanding of kiln technology in the American south region during the early nineteenth century and daily operations around the Pottersville kiln. This article provides a discussion of the archaeological findings from those investigations and postulates possibilities regarding the origins for kiln designs in the Old Edgefield District. This research revealed that African-American workers and European-American entrepreneurs constructed a type of kiln at Pottersville that was never seen before in the Americas.